Multidisciplinary approach to cancer care in Rwanda: the role of tumour board meetings - Niyibizi, Brandon A; Muhizi, Eulade; Rangira, Daniella; Ndoli, Diane A; Nzeyimana, Innocent N; Muvunyi, Jackson; Irakoze, Magnifique; Kazindu, Madeleine; Rugamba, Alex; Uwimana, Khadidja; Cao, Yuanzhen; Rugengamanzi, Eulade; et al. (Ecancermedicalscience, 2023)
Cancer treatment is complex and necessitates a multidisciplinary approach. Tumour Board Meetings (TBMs) provide a multidisciplinary platform for health care providers to communicate about treatment plans for patients. TBMs improve patient care, treatment outcomes and, ultimately, patient satisfaction by facilitating information exchange and regular communication among all parties involved in a patient's treatment. This study describes the current status of case conference meetings in Rwanda including their structure, process and outcomes. The study included four hospitals providing cancer care in Rwanda. Data gathered included patients' diagnosis, number of attendance and pre-TBM treatment plan, as well as changes made during TBMs, including diagnostic and management plan changes. From 128 meetings that took place at the time of the study, Rwanda Military Hospital hosted 45 (35%) meetings, King Faisal Hospital had 32 (25%), Butare University Teaching Hospital (CHUB) had 32 (25%) and Kigali University Teaching Hospital (CHUK) had 19 (15%). In all hospitals, General Surgery 69 (29%) was the leading speciality in presenting cases. The top three most presented disease site were head and neck 58 (24%), gastrointestinal 28 (16%) and cervix 28 (12%). Most (85% (202/239)) presented cases sought inputs from TBMs on management plan. On average, two oncologists, two general surgeons, one pathologist and one radiologist attended each meeting. TBMs in Rwanda are increasingly getting recognised by clinicians. To influence the quality of cancer care provided to Rwandans, it is crucial to build on this enthusiasm and enhance TBMs conduct and efficiency.